Salivary Cortisol Determination in ACTH Stimulation Test to Diagnose Adrenal Insufficiency in Patients with Liver Cirrhosis - Lara Albert; Joaquím Profitós; Jordi Sánchez-Delgado; Ismael Capel; José Miguel González-Clemente; David Subías; Albert Cano; Eugenio Berlanga; Anna Espinal; Marta Hurtado; Rocío Pareja; Mercedes Rigla; et al. (International Journal of Endocrinology)
Purpose. The prevalence of adrenal insufficiency (AI) in patients with decompensated liver cirrhosis is unknown. Because these patients have lower levels of cortisol-binding carrier proteins, their total serum cortisol (TSC) correlates poorly with free serum cortisol (FC). Salivary cortisol (SaC) correlates better with FC. We aimed to establish SaC thresholds for AI for the 250 μg intravenous ACTH test and to estimate the prevalence of AI in noncritically ill cirrhotic patients. Methods. We included 39 patients with decompensated cirrhosis, 39 patients with known AI, and 45 healthy volunteers. After subjects fasted ≥8 hours, serum and saliva samples were collected for determinations of TSC and SaC at baseline 0’(T0) and at 30-minute intervals after intravenous administration of 250 μg ACTH [30’(T30), 60’(T60), and 90’(T90)]. Results. Based on the findings in healthy subjects and patients with known AI, we defined AI in cirrhotic patients as SaC-T0< 0.08 μg/dL (2.2 nmol/L), SaC-T60 < 1.43 μg/dl (39.5 nmol/L), or ΔSaC<1 μg/dl (27.6 nmol/L). We compared AI determination in cirrhotic patients with the ACTH test using these SaC thresholds versus established TSC thresholds (TSC-T0< 9 μg/dl [248 nmol/L], TSC-T60 < 18 μg/dl [497 nmol/L], or ΔTSC<9 μg/dl [248 nmol/L]). SaC correlated well with TSC. The prevalence of AI in cirrhotic patients was higher when determined by TSC (48.7%) than by SaC (30.8%); however, this difference did not reach statistical significance. AI was associated with sex, cirrhosis etiology, and Child-Pugh classification. Conclusions. Measuring SaC was more accurate than TSC in the ACTH stimulation test. Measuring TSC overestimated the prevalence of AI in noncritically ill cirrhotic patients.